The correlation between cancer stem cells and epithelial-mesenchymal transition: molecular mechanisms and significance in cancer theragnosis - Lei, Zi-Ning; Teng, Qiu-Xu; Koya, Jagadish; Liu, Yangruiyu; Chen, Zizhou; Zeng, Leli; Chen, Zhe-Sheng; Fang, Shuo; Wang, Jinxiang; Liu, Yuchen; Pan, Yihang (Frontiers in Immunology, 2024)
The connections between cancer stem cells (CSCs) and epithelial-mesenchymal transition (EMT) is critical in cancer initiation, progression, metastasis, and therapy resistance, making it a focal point in cancer theragnosis. This review provides a panorama of associations and regulation pathways between CSCs and EMT, highlighting their significance in cancer. The molecular mechanisms underlined EMT are thoroughly explored, including the involvement of key transcription factors and signaling pathways. In addition, the roles of CSCs and EMT in tumor biology and therapy resistance, is further examined in this review. The clinical implications of CSCs-EMT interplay are explored, including identifying mesenchymal-state CSC subpopulations using advanced research methods and developing targeted therapies such as inhibitors and combination treatments. Overall, understanding the reciprocal relationship between EMT and CSCs holds excellent potential for informing the development of personalized therapies and ultimately improving patient outcomes.